Laboratory Assay of Brood Care for Quantitative Analyses of Individual Differences in Honey Bee (Apis mellifera) Affiliative Behavior - Shpigler, Hagai Y. (PLoS One, 2015)
Care of offspring is a form of affiliative behavior that is fundamental to studies of animal social behavior. Insects do not figure prominently in this topic because Drosophila melanogaster and other traditional models show little if any paternal or maternal care. However, the eusocial honey bee exhibits cooperative brood care with larvae receiving intense and continuous care from their adult sisters, but this behavior has not been well studied because a robust quantitative assay does not exist. We present a new laboratory assay that enables quantification of group or individual honey bee brood “nursing behavior” toward a queen larva. In addition to validating the assay, we used it to examine the influence of the age of the larva and the genetic background of the adult bees on nursing performance. This new assay also can be used in the future for mechanistic analyses of eusociality and comparative analyses of affilative behavior with other animals.